Dampak Pembelajaran Metode Diskusi terhadap Tingkat Pemahaman Mahasiswa - Arif, Arif; Nugraha, Rani (Nuances of Indonesian Language, 2022)
This study aims to explore the level of student comprehension in learning using the discussion method at Makassar State University. The discussion method is recognized as one of the effective learning approaches in improving students' critical thinking and communication skills. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and literature studies. The results show that the discussion method is well-liked by students, with good attendance in every meeting. However, there are challenges such as a lack of student focus, insufficient time for discussion, and emotional dynamics that can affect the outcome of the discussion. This research provides important insights into the implementation of the discussion method and its contribution to building a more knowledgeable society.